2010
DOI: 10.1186/1471-2407-10-189
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor and K-RAS status in two cohorts of squamous cell carcinomas

Abstract: BackgroundWith the availability of effective anti-EGFR therapies for various solid malignancies, such as non-cell small lung cancer, colorectal cancer and squamous cell carcinoma of the head and neck, the knowledge of EGFR and K-RAS status becomes clinically important. The aim of this study was to analyse EGFR expression, EGFR gene copy number and EGFR and K-RAS mutations in two cohorts of squamous cell carcinomas, specifically anal canal and tonsil carcinomas.MethodsFormalin fixed, paraffin-embedded tissues f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
49
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 42 publications
(61 reference statements)
8
49
0
4
Order By: Relevance
“…He observed increased EGFR expression in 21 patients in total, which presents 55% [21]. Several other studies were then published, finding EGFR expression between 58% -100% [22][23][24][25]. In our study we observed EGFR expression in one half of the patients.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…He observed increased EGFR expression in 21 patients in total, which presents 55% [21]. Several other studies were then published, finding EGFR expression between 58% -100% [22][23][24][25]. In our study we observed EGFR expression in one half of the patients.…”
Section: Discussionsupporting
confidence: 69%
“…Van Damme described EGFR expression 1+ in 7 patients, EGFR expression 2+ in 12 patients, and EGFR expression 3+ in 17 patients. In total, he observed EGFR expression in 83.7% patients [23]. We observed no EGFR Potential subjective influence on EGFR expression evaluation using immunohistochemistry should also be emphasized.…”
Section: Discussionmentioning
confidence: 96%
“…This lack of understanding is the primary factor hindering the effective use of these agents. In HNSCC, classical driver mutations of the pathway, such as PTEN and EGFR mutations, are rare, as are mutations in ERBB2-4 and members of the RAS pathway (23)(24)(25)(26)(27). To resolve this question, we undertook a detailed genomic dissection of the EGFR/PI3K pathway in oral cancer, the most common subsite of HNSCC.…”
mentioning
confidence: 99%
“…Mutations in EGFR (Hsieh et al, 2011;Szabó et al, 2011;Van Damme et al, 2010) and Ras (Hsieh et al, 2011;Murugan et al, 2012) and over expression of EGFR (Laimer et al, 2007), adaptor protein SHC (Plyte et al, 2000), G protein Rap (Mitra et al, 2003), and guanine nucleotide exchange factor SOS (Severino et al, 2008) have been reported in OSCC lesions. While none of the studies had investigated on the activating mutations in ERK2 gene, we observed and reported a single point mutation in the common docking domain of ERK2 (E322K) in an oral squamous cell carcinoma cell line in our previous study (Arvind et al, 2005).…”
Section: Discussionmentioning
confidence: 99%